PENGARUH DISIPLIN KERJA, LINGKUNGAN KERJA, DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PADA PT TIGARAKSA SATRIA.Tbk CABANG PADANG - Sari, Selvi Yona (Jurnal Ekobistek, 2017)
This research was conducted at PT. Tigaraksa Satria.Tbk Padang Branch, with the aim to determine the effect of work discipline, work environment, and work motivation either simultaneously or partially on the performance of employees at PT. Tigaraksa Satria.Tbk Padang Branch. The population in this study were all employees at PT. Tigaraksa Satria.Tbk Padang Branch totaled 50 people, and the data obtained by census method. Data analysis method used in this research is descriptive quantitative methods and multiple linear regression analysis using SPSS version 20.0. The results showed that the discipline of work, work environment and work motivation simultaneously have a positive and significant impact on employee performance. The magnitude of the effect of three independent variables together on the dependent variable of 60%, while 40% is influenced by other variables not examined in this study. Partial regression test results (t test) showed that the discipline of work, work environment and work motivation significantly positive effect on employee performance. As for the recommendations that the authors need to consider the work attendance and timeliness of work and provide motivation as reword against employees. Keywords: : Work Discipline, Work Environment, Work Motivation and Employee Performance